2021
DOI: 10.3390/microorganisms9091853
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Biofilm Activity of Bacteriophage K (ATCC 19685-B1) and Daptomycin against Staphylococci

Abstract: The purpose of the present study was to investigate anti-staphylococcal activity of daptomycin and bacteriophage K, alone or in combination, against biofilm-producers and non-producers S. aureus and S. epidermidis strains, under biofilm forming and cells’ proliferation conditions. Daptomycin and bacteriophage K (ATCC 19685B1), in different concentrations, were tested against 10 Staphylococcus aureus and 10 S. epidermidis, characterized by phenotypes and genotypes. The quantitative microtiter plate (crystal vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
(98 reference statements)
2
10
0
Order By: Relevance
“…Bacterial Growth rates were spectrophotometrically monitored [30,33] both in the presence and absence of different liposomal or drug solutions (MOX liposomes, empty liposomes, mixtures of free MOX, and empty liposomes or free MOX) at the MIC50 concentration of free MOX (0.15 µM). Briefly, overnight grown bacterial cells from a TSA agar plate were allowed to grow in fresh TSB broth (without glucose) to their early exponential phase.…”
Section: Bacterial Growth Curve Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial Growth rates were spectrophotometrically monitored [30,33] both in the presence and absence of different liposomal or drug solutions (MOX liposomes, empty liposomes, mixtures of free MOX, and empty liposomes or free MOX) at the MIC50 concentration of free MOX (0.15 µM). Briefly, overnight grown bacterial cells from a TSA agar plate were allowed to grow in fresh TSB broth (without glucose) to their early exponential phase.…”
Section: Bacterial Growth Curve Assaymentioning
confidence: 99%
“…The antibiofilm activity was evaluated at concentrations corresponding to the MIC of MOX, i.e., 0.3 µM, for all the formulations, according to previously reported methods [31][32][33]. Crystal violet (CV) staining and a validated MTT [3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide, a yellow tetrazole] cell viability assays were used to assess biofilm susceptibility to each free or liposomal MOX formulation.…”
Section: Biofilm Susceptibility Assaysmentioning
confidence: 99%
“…investigated the efficacy of daptomycin and bacteriophage K in killing S. aureus and S. epidermidis strains. [ 276 ] They noticed there were no dramatic disparities between species. However, daptomycin showed higher efficacy when using medium and high concentrations of the drug.…”
Section: State‐of‐the‐art Technologies For Prevention and Treatment O...mentioning
confidence: 99%
“…In one case, it has been reported that Dapto rapidly penetrates a Staphylococcus epidermidis biofilm [ 15 ]. It was also recently demonstrated in our laboratories that various Staphylococci strains showed lower MIC to Dapto, under biofilm-forming conditions, suggesting that Dapto is active in embedded cells [ 16 ]. Nevertheless, the development of some Dapto-insusceptible MRSA isolates has been reported [ 17 , 18 ], raising serious concerns and indicating the importance of developing novel strategies for antimicrobial therapeutics.…”
Section: Introductionmentioning
confidence: 96%
“…In this context, we investigate herein the development and optimization of liposomal Dapto and evaluate the antimicrobial activity of optimal Dapto-liposome types (compared to the free drug) against four Staphylococci strains. The strains were selected between 20 clinical isolates that were previously characterized and studied for their susceptibility towards Dapto; two strains were found to be less susceptible towards Dapto and two were more Dapto-susceptible; the three that were also methicillin-resistant were selected for use in the current study [ 16 ].…”
Section: Introductionmentioning
confidence: 99%